A Demand for Social Welfare of Formal Sector in the Municipal Area of Ubonratchatani, Ubon Ratchatani Province - Lasongyang, Weerayut (Naresuan University Law Journal, 2014)
In developed countries, the Government recognizes the important of the living of citizens to meet the elementary needs of the social welfare thoroughly with the system of Commonwealth. Constitution of the kingdom of Thailand from the past to present has established guidelines for the welfare of the state is called “Directive Principle of Fundamental State Policies” The study found that providing social welfare to the general public by the National Health Security Law. Which is not required to pay contributions, but have better than social welfare formal sector. For example, problems of requirements to change the payment of medical bills, problems of determine the criteria to pay contributions and issues with the extended scope of the disease, etc. This research is to propose a solution that is should be amended in the payment of medical bills from the Capitation system to the Fee For Service system. It should be modified to calculate the contributed by switching of real income. Formal sector should have been treated all diseases, even diseases that have a high cost as well as the National Health Insurance.